Assembling ionic liquids in MOF "Monomer" based membranes to trigger CO2/CH4 separation. (19th October 2022) - Cui, Xiaolei; Kang, Zixi; Fan, Weidong; Pang, Jia; Feng, Yang; Zhang, Caiyan; Yu, Liting; Liu, Shuo; Tang, Xiuxian; Fan, Lili; Wang, Rongming; Sun, Daofeng
Abstract : MOF composite membranes are prepared using the interfacial assembly method and functional modification of ILs to enhance the CO2 /CH4 sieving performance. Abstract : The advantages of ionic liquids (ILs) in the selective adsorption of CO2 can improve the CO2 -selective separation performance of IL-modified membranes. Herein, a facile post-modification strategy using ILs has been developed for filling the interspace of MOF "monomer" based membranes to enhance the CO2 /CH4 sieving performance. The membranes constructed via the interfacial polymerization of MOF "porous monomers" and trimesoyl chloride (TMC) have nanoscale interspaces, which limit the performance of these membranes in the field of precise CO2 /CH4 sieving. The addition of ILs with high CO2 affinity filled these interspaces between the MOF and TMC monomers, resulting in a CO2 /CH4 selectivity of 35 for the modified membranes compared with the non-selectivity of the pristine membrane. Furthermore, the hydrogen-bond interaction between ILs and the membrane improves the separation stability and avoids the loss of ILs during gas permeation. After long-term continuous gas separation tests, the membrane can maintain stable CO2 /CH4 selectivity. Therefore, a post-modification membrane using ILs is highly desirable for enhancing the gas separation performance of MOF "porous monomer" based membranes for natural gas purification applications.